Pengaruh Kualitas Pelayanan Dan Persepsi Harga Terhadap Kepuasan Konsumen Rony Barbershop Bantul - Rizky Ardiana Sukmawan; Bangun Putra Prasetya (Journal Economic Excellence Ibnu Sina, 2024)
Barbershop is a type of business that is skyrocketing. Taking the momentum of the return of the smooth era hair trend using pomade, the phenomenon of the proliferation of barbershops seems unstoppable. The type of research used in this research is a survey. In survey research, information is collected from respondents using a questionnaire totaling 102 respondents. This research aims to determine Service Quality and Price Perception together on consumer satisfaction of Rony Barbershop service users in Bantul City. There is an influence of service quality and price perception together on consumer satisfaction of Rony Barbershop service users in Bantul City. This is proven by the calculated F value of 36.153 with a significance of 0.000, therefore the significance value is smaller than 0.05.